The Concept of Scientific Revolution and Ottoman Empire - Mehmet Aysoy (İnsan & Toplum)
The emergence of modern science in science history is as important as the spread of it. In science history, the approach of ‘scientific revolution’ makes astronomy the trigometrical point and conceptualizes modernity from this center. While the reflection of developments arising from astronomy did not give the same effect, the reflections of developments in other sciences became prominent. And medicine comes the foremost in these fields. Although its development is discussable in early modernity, it has equivalents in Ottoman except for the west. In order to be able to evaluate this case, more open ended approaches need to be developed as regards the emergence and spread of modern science. In addition to scientific revolution term, the studies conducted in the field of medicine were assessed to mention about Islam/Ottoman medicine philosophy in this study. This subject must be assessed not only in terms of modernity but also in periods regarding the history of modernity. And; in this sense ‘early modernity adds a sociological context to the period entitled as ‘scientific revolution’. Early modernity is a period in which tradition as a conceptional solution tool is functional. Early modernity is a period in which ‘interfaces’ emerged and while it is the last representative of interface tradition; it is the first representative of modernity. In this context, the transfer of modern science out of west gains a context which can be assessed. The concept of scientific revolution determines important problems in the analysis of modernity.